To compare Uncomparable (about the Thesis of Regina Lakačauskaitė-Kaminskienė „The Modernization of the Living Space of the 20th Century Urban Resident. Two Cases: Interwar Kaunas and Soviet Vilnius“) - Šiupšinskas, Matas (Lietuvos istorijos studijos, 2018)
[text in Lithuanian]